SOFTWARE PRODUCT LINE MODELING MADE PRACTICAL. - Eriksson, Magnus; Börstler, Jürgen; Borg, Kjell (Communications of the ACM, 2006)
The article discusses an approach to computer software development that integrates case modeling and feature modeling to facilitate the creation of a software product line. Software product lines allow companies to improve development efficiency and cut costs by reusing assets throughout computer software offerings, while making products more cohesive for end-users. The authors examine the Swedish defense industry's use of software product line modeling to improve proprietary computer software.